Adaptive scaling ecosystem for system transformation: operationalizing solar-based farmer-led irrigation in Sub-Saharan Africa - Minh, Thai Thi; Schmitter, Petra (Elsevier, 2025)
Calls for greater conceptual clarity on how to scale innovation for food-system transformation are increasing. We develop an Adaptive Scaling Ecosystem (ASEco)–a framework that integrates system-based scaling with innovation-ecosystem thinking to enable system change. ASEco conceptualizes scaling as a dynamic, interconnected process organized around four functions—niche, reach, accelerate, transform—and guided by four principles of adaptability, reflectiveness, inclusiveness, and flexibility. It foregrounds subsystem interactions, contextual fit, and multi-layered cross-scale networks embedded in institutional and governance arrangements. ASEco enables multiple pathways that combine niche development, market reach, the acceleration of enabling environments, and transformative shifts in rules and norms. It translates food-system complexity into actionable levers by clarifying ecosystem boundaries, aligning actor networks with scaling functions, and fostering continuous adaptation through feedback and coevolution, thereby managing non-linear dynamics and trade-offs. In operationalizing ASEco, research-for-development organizations act as boundary spanners that orchestrate, drive, and facilitate adaptive scaling by aligning incentives, building trust, and enabling inclusive multistakeholder collaboration. We ground the framework in solar-based farmer-led irrigation development (SFLID) in sub-Saharan Africa to illustrate how evolving boundaries, agility, and adaptability support scaling that contributes to sustainable, cleaner food-system transformation. ASEco offers a practical, adaptable approach for designing, steering, and learning from adaptive scaling processes in complex food systems.